National summary reports on pesticide residue analysis performed in 2015. Issue 4 (11th April 2017) - ,
Abstract : This publication is linked to the following EFSA Journal article: http://onlinelibrary.wiley.com/doi/10.2903/j.efsa.2017.4791/full